HUBUNGAN ANTARA LOCUS OF CONTROL DAN KONSEP DIRI DENGAN KEMATANGAN KARIER SISWA DI SMK VETERAN - Siti Faizah; Nasehudin Nasehudin; Yeti Nurizzati (Academy of Education Journal, 2023)
This study aims to determine how big the relationship between locus of control and self-concept with career maturity of class XI students at SMK Veteran Cirebon City. This study uses a quantitative type by using an ex post facto research design, the sample used in this study was 62 respondents, the sample was taken using purposive non-random sampling. Data collection techniques in this study were carried out by means of observation, questionnaires, and documentation. Then analyzed by using multiple correlation hypothesis test to find out how big the relationship between locus of control and self-concept with students' career maturity. Based on the results of the study, it can be concluded that the results of the locus of control questionnaire recapitulation of students are 70.98% (good qualification), student self-concept is 75.65% (very good qualification) and student career maturity is 76.58% (very good qualification). The results of the correlation test between X1 and X2 with Y are 0.457 (sufficient correlation) with a significant level of 0.001 <0.05, it can be concluded that Ho is rejected and Ha is accepted, meaning that there is a relationship between locus of control and self-concept with career maturity of class student. XI in the Cirebon City Veterans Vocational High School significantly.